Relationship Between Juvenile Offenders' Psychosocial Maturity and Experienced Parenting Style - Alexander, Denesha (2019)
Juvenile delinquency continues to be a social ill with parents often being liable for their child's reprehensible behavior. In this nonexperimental, correlational study, the relationship between experienced parenting style and psychosocial maturity was examined in a sample of juvenile offenders receiving intensive in-home services. The General Theory of crime by Gottfredson and Hirshi provided the framework for the study along with parenting style typologies by Baumrind. Data were collected from a convenience sample of 60 11th grade juvenile offenders and their parent/caretakers using questionnaires. Multiple regression analysis was used to examine the data. The Psychosocial Maturity Index was used to measure psychosocial maturity, and the Parenting Skills Dimensions Questionnaire Short Version was used to measure experienced parenting style. Results indicated parenting style did not account for the variance in measures of psychosocial maturity. Stakeholders may benefit from an improved understanding of how measures of psychosocial maturity are impacted by parenting practices